2017
DOI: 10.5812/ircmj.14220
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Psychometric Evaluation of Questionnaire of Influencing Factors of Nursing Students’ Clinical Judgment: A Mixed Method Study in an Iranian Context

Abstract: Background: Identification of the influencing factors of nursing students' clinical judgment (CJ) facilitates the achievement of this important educational outcome. However, no tool is so far designed to assess it in the field of clinical education in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…However, in the original study of the design of the questionnaire, no report was submitted regarding the conduct Test-retest and stability of this questionnaire (25). In examining the construct validity and exploratory and confirmatory factor analysis, the high KMO and goodness of the model were the strengths of this study and revealed the high quality of factor analysis to determine the factors (21). Most of the nurses expressed difficulty understanding study results in the research journals, as the biggest barrier, and personalized search, as the least skill.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, in the original study of the design of the questionnaire, no report was submitted regarding the conduct Test-retest and stability of this questionnaire (25). In examining the construct validity and exploratory and confirmatory factor analysis, the high KMO and goodness of the model were the strengths of this study and revealed the high quality of factor analysis to determine the factors (21). Most of the nurses expressed difficulty understanding study results in the research journals, as the biggest barrier, and personalized search, as the least skill.…”
Section: Discussionmentioning
confidence: 93%
“…Also, the average of scale content validity index (SCVI/Ave) was calculated as 0.9, that is acceptable (21). In examining the reliability of the questionnaire, internal consistency, Cronbach's alpha was 0.92 of the entire questionnaire and within acceptable limits that were satisfactory (22).…”
Section: Discussionmentioning
confidence: 99%
“…The COSMIN checklist (COnsensus-based Standards for selecting health status Measurement Instruments and how to select an outcome measurement instrument and COSMIN Study Design checklist for Patient-reported outcome measurement instruments) (Mokkink et al, 2016(Mokkink et al, , 2019(Mokkink et al, , 2020 Also, teaching and learning CJ is carried out through NP care planning (Sommer, 2020). The IFNSCJ covers four main factors; thoughtful monitoring, informational and ethical facilitators, educational and environmental facilitators and collaborative care, all of which influence the CJ in nursing students (Pouralizadeh et al, 2017). A group of 134 undergraduate nursing students who had received NP course, completed the SSW-NCP survey and IFNSCJ questionnaire.…”
Section: Phase Iii: Reliability and Convergent Validitymentioning
confidence: 99%
“…was additionally used to determine the reliability and validity of the adapted Persian version of SSW-NCP in undergraduate nursing students of a local nursing school from December 2020 to May 2021. Reliability of the instrument was assessed using Cronbach's Alpha coefficient (α) for internal consistency using an independent group of 30 undergraduate nursing students.Twenty undergraduate nursing students completed two SSW-NCP surveys across the specified time frame of 1 month between assessments, and Pearson's correlation coefficients (r) and intraclass correlation coefficients (ICCs) using two-way mixed-effects model absolute agreement were calculated.Convergent validity was evaluated by comparison of the instrument to an existing instrument that was measuring the most similar construct, the SSW-NCP survey to the Influencing Factors of Nursing Students' Clinical Judgment (IFNSCJ) questionnaire(Pouralizadeh et al, 2017) based on their probable correlations. The concept of clinical judgement (CJ) is considered as a problem-solving activity adopted to the NP model as a consequence (Alfaro-LeFevre, 2019).…”
mentioning
confidence: 99%
“…The lack of suitability is due to a mismatch of content, context, and culture ( Dörnyei and Dewaele, 2022 ; Kemerli and Celik, 2017 ). Another questionnaire was constructed by Pouralizadeh et al (2017) to measure the influencing factors of clinical judgment in nursing students. This questionnaire includes 38 items and four factors of thoughtful monitoring, informational and ethical facilitators, educational and environmental facilitators, and collaborative care.…”
Section: Introductionmentioning
confidence: 99%